An Interview on District and School Transformation: Practical Approaches to Facilitating Sustainable Systemic Change. Issue 1 (February 2022) - Schneider, Kurt A.; Sands, Suzanne; Endre, Kristen; Baker, Dale; Burnette, Kristin; Ryndak, Diane
Illinois has an education system that includes regional cooperatives charged with supporting member districts in the provision of special education services for students from birth to age 22. Such support can include both direct services (i.e., early childhood services, special education classes in a separate building or in special education classrooms of the member districts) and indirect services (e.g., consulting services, professional development and coaching, assessment, related services). This interview is with three leaders in one such cooperative of 18 K-8 and high school member districts of varying size across 3 regions in 2 counties.